Prevalence, risk factors, and outcomes of malnutrition in older adults hospitalized with community-acquired pneumonia: a retrospective study - Zheng, Xiao-lu; Zhang, Xing; Yuan, Jia-hui; Yi, Lu-tian (Frontiers in Medicine, 2025)
PurposeCommunity-acquired pneumonia (CAP) is a common health problem in older adults. Malnutrition is also prevalent in the elderly population. This study aimed to investigate the prevalence, risk factors, and outcomes of malnutrition in hospitalized older adults diagnosed with CAP.MethodsFrom April 2023 to October 2023, clinical data of older adults hospitalized with CAP were retrospectively analyzed. Based on their malnutrition status at the time of admission, patients were classified into the malnutrition and non-malnutrition groups. The demographic and clinical characteristics as well as outcomes were compared between the two groups. Univariate and multivariate logistic regression analyses were used for variables of interest. The receiver operating characteristic curve was applied to evaluate the risk factors.ResultsA total of 511 eligible patients were included in this study. There were 90 and 421 patients in the malnutrition and non-malnutrition groups, respectively. Univariate analysis showed a significant difference in six factors: age, living alone, past cerebral stroke, Parkinson’s disease, serum albumin, and hemoglobin (P < 0.05). Multivariate analysis revealed that age (OR = 1.044, P = 0.025), past cerebral stroke (OR = 2.643, P = 0.014), Parkinson’s disease (OR = 2.998, P = 0.028), low serum albumin level (OR = 6.407, P < 0.001), and low hemoglobin level (OR = 4.629, P < 0.001) were independent risk factors for malnutrition. Receiver operating characteristic curve analysis of age, serum albumin level, and hemoglobin level showed a cutoff value of 74 years, 40.5 g/L, and 105 g/L, respectively.ConclusionThe prevalence of malnutrition was high in older adults hospitalized with CAP. Malnutrition was associated with worse outcomes, including prolonged hospital stay, higher in-hospital mortality, and increased readmission. Old age (> 74 years), past cerebral stroke, Parkinson’s disease, low serum albumin level (< 40.5 g/L), and low hemoglobin level (< 105 g/L) were regarded as independent risk factors.